Peningkatan Pemecahan Masalah Dan Hasil Belajar Matematika Melalui Aplikasi Exe(e-learning XHTML editor)Pada Siswa Kelas VIIIE SMP Negeri 1 Geyer Tahun Ajaran 2015/2016 - Kristina Yulinda, Meta, Masduki, S.Si, M.Si (2015)
This research aims to improve problem solving and learning outcomes in mathematics using e-learning with applications eXe (e-learning XHTML editor). Subjects recipient of action is class VIII E SMPN 1 Geyer with 28 students (14 male students and 14 female students), the teacher as the subject of the perpetrator, the researcher as an observer. Data collection method used are observation, field notes, interviews, documentation and testing. Data analysis techniques use reduction, data presentation and conclusion.Results ofthe studyare basedon indicators ofproblem solving and learning outcomes mathematics an increase was found that: (1) ability to demonstrate understanding of the problem, before the act of 13 students (46.429%) after the action increased to 25 students (89.286%), (2) ability to organize data and choose the relevant information in problem solving, before action 10 students (35.714%) after the action increased to 23 students (82.143%), (3) the ability to develop problem solving strategies before action 6 students (21.429%) after the action increased to 24 students (85.714 %), (4) the ability of the students do tests completed KKM before action of 12 students (42.857%) after the action increased to 28 students (100%).